2015
DOI: 10.1016/j.ymgme.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The alpha-galactosidase A p.Arg118Cys variant does not cause a Fabry disease phenotype: Data from individual patients and family studies

Abstract: Summary Lysosomal α-galactosidase A (α-Gal) is the enzyme deficient in Fabry disease (FD), an X-linked glycosphingolipidosis caused by pathogenic mutations affecting the GLA gene. The early-onset, multi-systemic FD classical phenotype is associated with absent or severe enzyme deficiency, as measured by in vitro assays, but patients with higher levels of residual α-Gal activity may have later-onset, more organ-restricted clinical presentations. A change in the codon 118 of the wild-type α-Gal sequence, replaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 47 publications
4
81
0
2
Order By: Relevance
“…Since they are already in dialysis, histological confirmation of Fabry nephropathy is not an option, and ESRD itself may explain most coexistent cardiac or central nervous system involvements. In this regard, the prevalence of the R118C GLA variant (5 of 3,650, 0.14%) in Spanish hemodialysis patients was reported to be similar to the prevalence found in Portuguese healthy subjects (1 of 696; 0.14%), and most patients with the R118C variant do not have features of FD [10,11]. Thus, it is unlikely that Fabry nephropathy explains the ESRD of R118C patients identified in the Spanish hemodialysis screening [10,12].…”
Section: Introductionsupporting
confidence: 56%
“…Since they are already in dialysis, histological confirmation of Fabry nephropathy is not an option, and ESRD itself may explain most coexistent cardiac or central nervous system involvements. In this regard, the prevalence of the R118C GLA variant (5 of 3,650, 0.14%) in Spanish hemodialysis patients was reported to be similar to the prevalence found in Portuguese healthy subjects (1 of 696; 0.14%), and most patients with the R118C variant do not have features of FD [10,11]. Thus, it is unlikely that Fabry nephropathy explains the ESRD of R118C patients identified in the Spanish hemodialysis screening [10,12].…”
Section: Introductionsupporting
confidence: 56%
“…This approach identifies pathogenic and benign variants of the GLA gene and provides a discriminating method to identify patients truly affected by Fabry disease. 30,31 On the other hand, our study demonstrates that analysis of enzyme activity or the amount of substrate in the urine alone lacks the required specificity for large-scale screening. Urinary Gb 3 was elevated in about 15% of patients with heart disease who otherwise did not have GLA mutations, 20 and it is known to be normal in patients with mild mutations and in females, 29 or is falsely elevated for other reasons.…”
Section: Discussionmentioning
confidence: 88%
“…However, more comprehensive and critical investigations showed that these variants do not definitively lead to Fabry disease-related complications. 31,36 D83N is a novel variant, but the patient had normal urine Gb 3 levels and no other characteristics of Fabry disease. This variant was found to have high residual α-galactosidase A activity in the HEK-293 in vitro assay.…”
Section: Discussionmentioning
confidence: 89%
“…Second: in females coinheriting a negatively acting GLA 5 0 UTR SNP in trans with a pathogenic GLA mutation, the compound heterozygosity may significantly decrease the REA and aggravate the clinical phenotype since the aGal activity would be subnormal in all cells, irrespective of which of the two X chromosomes is inactivated. Third: in individuals carrying GLA variants associated with small decreases in REA, which otherwise would not be the cause of FD clinical phenotypes -like the p.Arg118Cys (Ferreira et al 2015) and the p.Asp313Tyr (Yasuda et al 2003;Niemann et al 2013) -the additive effect of a negatively acting GLA 5 0 UTR SNP in cis could decrease REA into the typical range of mutations associated with later-onset phenotypic variants of FD (Ferreira et al 2015), thereby modifying the expected phenotype. This might also affect the probability of identifying individuals carrying such mutations in large case-finding studies of FD among high-risk patients, when the primary screening method is based on aGal activity analysis.…”
Section: Discussionmentioning
confidence: 99%